Power-sharing: A gender intervention. Issue 1 (January 2020) - McCulloch, Allison
Power-sharing may be a leading model for the inclusion of ethnic minorities in post-conflict government, but it is also considered a gender-blind approach to conflict regulation. In this article, I identify recent openings and shifts in power-sharing theory that suggest a new receptivity to the adoption of a gender perspective. Specifically, I focus on two major developments that have emerged over the last three decades – the widening of the power-sharing universe and the refinement of its institutional prescriptions – which have opened up analytical and political space for the inclusion of women in power-sharing theory. Building on these developments, I identify extant gender gaps in power-sharing theory, discuss strategies for overcoming them through the adoption of what I call least-ascriptive-most-prescriptive rules, and outline areas for future research on integrating a gender perspective into power-sharing theory and practice. While power-sharing theory may initially appear resistant to a gender intervention, I demonstrate there is new analytical space in the theory for such a venture.